Architectural photographs as agents of travel and information. Virgil Bierbauer travels to circulate visual information in the Architectural Press in Interwar Hungary - Sebestyén, Ágnes Anna (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
Architectural photographs were circulated extensively in professional networks and the printed press during the interwar period to disseminate the latest news about modern architecture. In addition to contributing to the accumulation of pictorial information about buildings, these images were substitutes for travel while also stimulating the desire to explore. Ter es Forma (Space and Form), a leading architectural periodical, publicised international modern architecture in interwar Hungary, and was under the editorship of the architect Virgil Bierbauer between 1928 and 1942. Bierbauer established a continuously growing international network of connections that facilitated the distribution of his own works in the international architectural press as well as the acquisition of information about the activities of his contemporaries. Although he never managed to go overseas, Bierbauer was an avid traveller and his network covered not only Europe but also the United States and Japan. He took study trips in order to visit particular buildings, urban ensembles and exhibitions as well as to participate in congresses. He also took the opportunity to study the built environment during his holidays. Although he was an amateur photographer himself, he preferred to publish images by professional photographers in his journal. I argue that by facilitating the flow of information, architectural photographs served as substitutes for travel. Thus, I place the notion of travel as an analogy for both the transfer and the reception of modern architecture via photographic images in the magazine Teres Forma. In addition, I trace Bierbauer's attitude towards actual travel and the notion of travel with different case studies and how his approach permeated the printed page. I also analyse Bierbauer's own travels and how his experiences affected his editorial activities in terms of layout and content.